Extravasation Injuries in Adults. (8th May 2013) - Al-Benna, S.; O'Boyle, C.; Holley, J.
Abstract : Insertion of an intravascular catheter is one of the most common invasive procedures in hospitals worldwide. These intravascular lines are crucial in resuscitation, allow vital medication to be administered, and can be used to monitor the patients' real-time vital parameters. There is, however, growing recognition of potential risks to life and limb associated with their use. Medical literature is now replete with isolated case reports of complications succinctly described by Garden and Laussen (2004) as "An unending supply of "unusual" complications from central venous catheters." This paper reviews complications of venous and arterial catheters and discusses treatment approaches and methods to prevent complications, based on current evidence and endeavours to provide information and guidance that will enable practitioners to prevent, recognise, and successfully treat extravasation injuries in adults.